An Analysis Upon Effect of Physical and Psychological Implications on the Health of Child Labor: Examining the Impact of Child Labour on Physical and Psychological Health in Developing Countries (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Child labour is a worldwidephenomenon but more focus is required on developing countries. The policyframework of International Labour Organization (ILO) to eliminate child labouris based on United Nations (UN) Declaration of Fundamental Principles andRights at work (1998). Over 170 million children worldwide still work in orderto sustain their basic needs. About 22000 working children die due tooccupational hazards every year, as per ILO estimates. Indian population hasmore than 17.5 million working children in different industries, and maximumare in agricultural sector, leather industry, mining and match makingindustries etc. As per provisions in the Constitution of India, “the Stateshall direct its policy towards protection of childhood and youth againstexploitation and they shall not be employed to work in any factory or mine orengaged in any hazardous employment”; but unfortunately India has the largestnumber of urban and rural child workers in the world India being a developingnation is faced with traditional public health problems like communicablediseases, malnutrition, poor environmental sanitation and inadequate medicalcare. However, globalization and rapid industrial growth in the last few yearshas resulted in emergence of occupational health related issues. The majoroccupational diseases/morbidity of concern in India are silicosis,musculo-skeletal injuries, coal workers’ pneumoconiosis, chronic obstructivelung diseases, asbestosis, by sinuses, pesticide poisoning and noise inducedhearing loss. There are many agencies like National Institute of OccupationalHealth, Industrial Toxicology Research Centre, Central Labour Institute, etc.are working on researchable issues like Asbestos and asbestos related diseases,Pesticide poisoning, Silica related diseases other than silicosis andMusculoskeletal disorders. Still much more is to be done for improving theoccupational health research. The measures such as creation of advancedresearch facilities, human resources development, creation of environmental andoccupational health cells and development of database and information systemshould be taken.